Surfing reserves: a rapid diagnostic of potential sites on the coast of São Paulo State, Southeast Brazil - Cabrera, Gabriela [UNESP]; de Souza Abessa, Denis Moledo [UNESP] (Springer Nature, 2022)
Coastal zones are influenced by several anthropogenic pressures, and the resulting environmental impacts not only affect ecosystems but also have social and economic implications. The protection of coastal environments, including surf breaks, demands the development of governance mechanisms that encourage the establishment of local public policies and shared management involving local stakeholders; these measures address the ecological relevance of such environments and numerous human activities. Considering the surf as a relevant factor for coastal conservation and the surfer as a stakeholder, the non-profit organization Save the Waves Coalition (STW) created the World Surfing Reserves (WSR) program aimed at identifying and preserving surf ecosystems. This investigation aimed to diagnose and compare the potential of four pre-selected beaches from the State of São Paulo (Brazil) to become surfing reserves, according to the criteria established by the STW: a) wave quality, b) surf culture, c) environmental quality, and d) governance. The analysis consisted of literature review, field observations, and interviews with local stakeholders. The studied beaches present conditions that are good for surfing reserves, including high quality and frequency of waves, good environmental conservation, and well-developed surf culture. To some degree, the local communities of all the beaches are involved in participative management processes; however, in Itamambuca Beach, the community is mobilized to propose this beach as a candidate surfing reserve. Based on the topics analyzed, Itamambuca currently presents the best conditions for becoming a WSR.
Keywords: Coastal management; Conservation; Environmental governance; Surf